3D Medical Imaging by using Point Cloud Generation - Loures, Luiza; Patrocínio Jr., Zenilton Kleber G. do; Guimarães, Silvio Jamil F. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2025: Anais Estendidos da XXXVIII Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2025.38304, 2025)
Three-dimensional (3D) reconstruction of anatomical structures from medical images represents a significant advancement in the healthcare field—a topic already explored in various studies. Traditional methods often rely on contrastenhanced computed tomography (CT), which is contraindicated for certain patients. To address this limitation, this work proposes a new methodology for 3D lung modeling. The method consists in generating a unified point cloud from segmented CT slices, followed by the construction of a polygonal mesh using Poisson surface reconstruction. To enhance result visualization, a graphical user interface was developed to simultaneously display the reconstructed 3D model and the original DICOM slices. The results of this new approach confirm the feasibility of the project, establishing an alternative method for the 3D representation of lungs.